SOCIALLY-ENGINEERING ACTIVITY IN THE INFORMATION EPOCH - L. F. Matronina; A. N. Agafonov (Российский технологический журнал)
This article aims at identifying the dynamics of socioengineering activities in the information age, its possibilities and prospects. Conceptual analysis of contemporary approaches to social engineering undertaken by the authors showed that despite the discrepancies it should be considered as the direction of scientific research, on one hand, and as one of the leading mechanisms of transformation of social structures and social institutions, on the other hand. The authors take into account the results of research in the field of social engineering by leading experts and believe that there are a number of issues that require further development and concretization. Based on scientific methods (the method of systemic functional analysis, the comparative-analytical method, the hermeneutic approach and others) the article considers the features of social forecasting as a part of social engineering activities, describes the basic mechanisms of their influence on the attitude of public opinion capable of giving rise to anthropological risks and leading to a threat for information security. Given the contradictory nature of the social engineering activities in the information age, the authors come to the conclusion that one of the urgent problems of contemporary interdisciplinary studies is a competent examination of humanitarian social engineering assessment activities, including social programming to determine the degree ricorderai components and possibilities of their reduction.